Arrival timing diagnostics at a soft X‐ray free‐electron laser beamline of SACLA BL1. (1st April 2019) - Owada, Shigeki; Nakajima, Kyo; Togashi, Tadashi; Katayama, Tetsuo; Yumoto, Hirokatsu; Ohashi, Haruhiko; Yabashi, Makina
Abstract : Arrival timing diagnostics between a soft X‐ray free‐electron laser and synchronized optical laser pulses were performed at SACLA BL1. Abstract : An arrival timing monitor for the soft X‐ray free‐electron laser (XFEL) beamline of SACLA BL1 has been developed. A small portion of the soft XFEL pulse is branched using the wavefront‐splitting method. The branched FEL pulse is one‐dimensionally focused onto a GaAs wafer to induce a transient reflectivity change. The beam branching method enables the simultaneous operation of the arrival timing diagnostics and experiments. The temporal resolution evaluated from the imaging system is ∼22 fs in full width at half‐maximum, which is sufficient considering the temporal durations of the soft XFEL and the optical laser pulses.